2007
DOI: 10.1080/00016340601185301
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity level and weight gain in a cohort of pregnant Norwegian women

Abstract: Pregnant women have a low total physical activity level, and a high percentage of women exceed the recommended weight gain during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
111
4
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 29 publications
15
111
4
6
Order By: Relevance
“…Women in both groups ate much more fruit than is recommended, both at baseline and after those in the intervention group had received education. However, too much fruit can increase the risk of obesity and can even induce GDM [25]. The nut intake was higher than recommended values at baseline in both groups, but it subsequently fell among women who had received the intervention.…”
Section: Discussionmentioning
confidence: 96%
“…Women in both groups ate much more fruit than is recommended, both at baseline and after those in the intervention group had received education. However, too much fruit can increase the risk of obesity and can even induce GDM [25]. The nut intake was higher than recommended values at baseline in both groups, but it subsequently fell among women who had received the intervention.…”
Section: Discussionmentioning
confidence: 96%
“…More than 50% of the women in our study reported regular exercise at least once a week during the third trimester. Walking as exercise was included in this question and was the activity reported most frequently [13]. The number of women participating in general fitness activities corresponds with results from another Scandinavian study of pregnant women [14].…”
Section: Discussionmentioning
confidence: 99%
“…Dies erleichtert die Entbindung und das Wochenbett. Darüber hinaus wird einer übermä ßigen Gewichtszunahme in der Schwangerschaft entgegengewirkt und nach der Schwangerschaft wird das frühere Gewicht häufiger wieder erreicht [29]. Die erwünschten Gewichtszunahmen sind aus .…”
Section: Effekte Und Mögliche Gefahren Durch Körperliche Aktivität (Ka)unclassified
“…Eine randomisierte und kontrollierte Studie [27] wurde mit gesunden Frauen durchgeführt und bestand in einem zu Hause durchgeführten Ausdauertrainigsprogramm auf dem Fahrradergome ter gegenüber einer Kontrollgruppe (unterschiedlicher Fitnessgrad, unterschiedlicher BMI: [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Von der 20.…”
Section: Effekte Und Mögliche Gefahren Durch Körperliche Aktivität (Ka)unclassified